Quarrying in western Norway : an archaeological study of production and distribution in the Viking period and Middle Ages - Baug, Irene (Archaeopress archaeology., 2015)
The theme of this study is the large-scale exploitation of different stone products that took place in Norway during the Viking age and the Middle Ages (c. AD 800-1500). The research is based on analyses of two different quarry landscapes in western Norway: the quernstone quarries in Hyllestad, Sogn og Fjordane, and the bakestone quarries in Olve and Hatlestrand, Hordaland. The centre of attention is the production of utility artefacts: quernstones, millstones and bakestones, as well as more symbolic products such as stone crosses.